2nd hand reading William Kentridge - Kentridge, William 1955- (Fourthwall Books, 2014)
South African artist William Kentridge draws on varied sources in his work, including philosophy, literature, early cinema, theatre and opera. This publication began life as a film constructed from a succession of drawings made in 2013 on the pages of old books; a second-hand reading in which books are translated into a filming of books, articulating the relationship between drawing, photography and film-making. It is both a narrative and an acknowledgement of the necessity of repetition, inconsistency and the illogical. Kentridge has made many flip books, but at 800 pages this is his most ambitious. He has also been making animated films for two decades.0
Keywords: Kentridge, William / 1955-; Kentridge, William -- 1955-; Geschichte 2013; Art and literature; Zeichnung; Verfremdung; Übermalung; Künstlerbuch; Bildband